Alpha-fetoprotein-L3 and Golgi protein 73 may serve as candidate biomarkers for diagnosing alpha-fetoprotein-negative hepatocellular carcinoma - Xu, Wanju; Zhang, Zhiguo; Zhang, Yanying; Wang, Yeying; Xu, Lingling (OncoTargets and therapy, 2016)
Currently, there is no reliable biomarker for use in diagnosing alpha-fetoprotein (AFP)-negative hepatocellular carcinoma (HCC). Such a biomarker would aid in making an early diagnosis of AFP-negative HCC, ensuring the timely initiation of treatment. This study examined AFP-L3 and Golgi protein 73 (GP73) as candidate biomarkers for AFP-negative HCC. The affinity adsorption method and enzyme-linked immunoassays were separately used to determine serum levels of AFP-L3 and GP73 in 50 patients with AFP-negative HCC, 30 non-HCC patients, and 50 healthy subjects. Fifty percent of patients with AFP-negative HCC tested positive for AFP-L3, while 3.33% of non-HCC patients and 2.00% of healthy subjects were AFP-L3 positive. Patients with AFP-negative HCC had significantly higher serum levels of AFP-L3 compared to non-HCC patients and healthy individuals; however, there was no significant difference in the AFP-L3 levels of non-HCC patients and healthy subjects. Sixty-six percent of patients with AFP-negative HCC tested positive for GP73, while 10% of non-HCC patients and 0% of healthy subjects were GP73-positive. Patients with AFP-negative HCC had significantly higher serum levels of GP73 compared to non-HCC patients and healthy subjects, but there was no significant difference between the GP73 levels of non-HCC patients and healthy individuals. Moreover, 20 patients with AFP-negative HCC were both AFP-L3- and GP73-positive, while no non-HCC patients or healthy subjects tested positive for both markers. Either AFP-L3 or GP73 may be used as a biomarker for diagnosing AFP-negative HCC, while their combined use provides improved diagnostic accuracy and greater sensitivity.